2014
DOI: 10.1002/stem.1746
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine Eliminates Cancer Stem Cells Through Deregulation of Jak2 and DNMT1

Abstract: Triple negative breast cancer (TNBC) is known to contain a high percentage of CD44+/CD24−/low cancer stem cells (CSC), corresponding with a poor prognosis despite systemic chemotherapy. Chloroquine (CQ), an anti-malarial drug, is a lysotropic reagent which inhibits autophagy. CQ was identified as a potential CSC inhibitor through in silico gene expression signature analysis of the CD44+/CD24−/low CSC population. Autophagy plays a critical role in adaptation to stress conditions in cancer cells, and is related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 46 publications
4
82
0
Order By: Relevance
“…Consistent with these data, a recent study showed that the anti-malarial drug chloroquine inhibits Jak2/STAT3 signaling, decreases the MSFE in a number of TN breast cancer cell lines, and decreases the TIC frequency in MDA231 xenograft tumors (Choi, et al 2014). Importantly, it has also been shown that breast TIC-derived IL-6 recruits mesenchymal stem cells, which communicate with breast TICs by secreting additional cytokines and chemokines, creating a breast TIC-promoting microenvironment (Liu, et al 2011).…”
Section: Pathways That Regulate Breast Tics and Confer Resistancesupporting
confidence: 55%
“…Consistent with these data, a recent study showed that the anti-malarial drug chloroquine inhibits Jak2/STAT3 signaling, decreases the MSFE in a number of TN breast cancer cell lines, and decreases the TIC frequency in MDA231 xenograft tumors (Choi, et al 2014). Importantly, it has also been shown that breast TIC-derived IL-6 recruits mesenchymal stem cells, which communicate with breast TICs by secreting additional cytokines and chemokines, creating a breast TIC-promoting microenvironment (Liu, et al 2011).…”
Section: Pathways That Regulate Breast Tics and Confer Resistancesupporting
confidence: 55%
“…Previous studies have demonstrated that the potential mechanisms for the antitumor effects of CQ may include the inhibition of autophagy (22), the induction of apoptosis (23,24), the elimination of cancer stem cells (25), the normalization of vasculature (26), the enhancement of the immune response (27) and the arrest of cell cycle progression (22). The focus of the present study was primarily on the apoptosis, cell cycle distribution and autophagy induced by CQ treatment.…”
Section: Discussionmentioning
confidence: 95%
“…In order to verify whether modulation of 4 autophagy could reduce the 'stemness' or induce apoptosis of CSCs, we treated ALDH hi cells with 5 CQ, a well-known autophagy inhibitor which can impair endosomal acidification, block endosome 6 and autophagosome fusion with lysosomes, and result in accumulation of LC3-II and p62 proteins 7 (p62 is an adaptor protein that delivers specific ribosomal and bulk ubiquitinated cytosolic 8 proteins to autolysosomes, eventually being delivered to lysosomes for degradation) [38][39]. As 9 shown in Fig.…”
Section: Inhibition Of Autophagy Reduces the 'Stemness' Of Breast Canmentioning
confidence: 99%